Cladribine in combination with entinostat synergistically elicits anti-proliferative/anti-survival effects on multiple myeloma cells. Issue 8 (18th April 2018) - Wang, Bolun; Lyu, Hui; Pei, Shanshan; Song, Deye; Ni, Jiangdong; Liu, Bolin
ABSTRACT: Cladribine (2CdA), a synthetic purine analog interfering with DNA synthesis, is a medication used to treat hairy cell leukemia (HCL) and B-cell chronic lymphocytic leukemia. Entinostat, a selective class I histone deacetylase (HDAC) inhibitor, shows antitumor activity in various human cancers, including hematological malignancies. The therapeutic potential of cladribine and entinostat against multiple myeloma (MM) remains unclear. Here we investigate the combinatorial effects of cladribine and entinostat within the range of their clinical achievable concentrations on MM cells. While either agent alone inhibited MM cell proliferation in a dose-dependent manner, their combinations synergistically induced anti-proliferative/anti-survival effects on all MM cell lines (RPMI8226, U266, and MM1.R) tested. Further studies showed that the combinations of cladribine and entinostat as compared to either agent alone more potently induced mitotic catastrophe in the MM cells, and resulted in a marked increase of the cells at G1 phase associated with decrease of Cyclin D1 and E2F-1 expression and upregulation of p21 waf−1 . Apoptotic ELISA and western blot analyses revealed that the combinations of cladribine and entinostat exerted a much more profound activity to induce apoptosis and DNA damage response, evidenced by enhanced phosphorylation of histone H2A.X and the DNA repair enzymes Chk1 and Chk2. Collectively, our data demonstrate that the combinations of cladribine and entinostat exhibit potent activity to induce anti-proliferative/anti-survival effects on MM cells via induction of cell cycle G1 arrest, apoptosis, and DNA damage response. Regimens consisting of cladribine and/or entinostat may offer a new treatment option for patients with MM. Abbreviations: MM, multiple myeloma; HCL, hairy cell leukemia; HDAC, histone deacetylase; Ab, antibody; mAb, monoclonal Ab; FBS, fetal bovine serum; CI, combination index; PAGE, polyacrylamide gel electrophoresis; ELISA, enzyme-linked immunosorbent assay; PARP, poly(ADP-ribose) polymerase; MTS, 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, inner salt